Retinoic Acid and the Gut Microbiota in Alzheimer’s Disease: Fighting Back-to-Back? - Endres, Kristina (Current Alzheimer Research, 2019)
Background: There is growing evidence that the gut microbiota may play an important role in neurodegenerative diseases such as Alzheimer’s disease. However, how these commensals influence disease risk and progression still has to be deciphered. Objective: The objective of this review was to summarize current knowledge on the interplay between gut microbiota and retinoic acid. The latter one represents one of the important micronutrients, which have been correlated to Alzheimer’s disease and are used in initial therapeutic intervention studies. Methods: A selective overview of the literature is given with the focus on the function of retinoic acid in the healthy and diseased brain, its metabolism in the gut, and the potential influence that the bioactive ligand may have on microbiota, gut physiology and, Alzheimer’s disease. Results: Retinoic acid can influence neuronal functionality by means of plasticity but also by neurogenesis and modulating proteostasis. Impaired retinoid-signaling, therefore, might contribute to the development of diseases in the brain. Despite its rather direct impact, retinoic acid also influences other organ systems such as gut by regulating the residing immune cells but also factors such as permeability or commensal microbiota. These in turn can also interfere with retinoid-metabolism and via the gutbrain- axis furthermore with Alzheimer’s disease pathology within the brain. Conclusion: Potentially, it is yet too early to conclude from the few reports on changed microbiota in Alzheimer’s disease to a dysfunctional role in retinoid-signaling. However, there are several routes how microbial commensals might affect and might be affected by vitamin A and its derivatives.
Keywords: mucosa